An Envenoming Syndrome from Massive Vespa Stings Induces Multiple Organ Failure - Tse-Hao Chen (Insects, 2020)
Envenoming syndrome is a systemic reaction induced by inoculation of large volumes of Hymenoptera venom. The clinical manifestations range from skin allergic reactions to multiple organ failure. Vespid venom-induced toxic reactions and anaphylaxis are the most common lethal mechanism of death, involving acute respiratory failure, acute liver failure, rhabdomyolysis, acute kidney injury, and severe coagulopathy. Multiple organ failure as a consequence of severe venom toxicity is a rare but dangerous complication in victims. Delay of intervention to correct vespid venom-induced toxic reactions may cause catastrophic complications. Here, we describe a case presenting a rare vespid venom-induced multiple organ failure with systemic coagulopathy after massive Vespa attack.